Motivation and self-efficacy are pivotal in driving science learning outcomes: Motivasi dan efikasi diri sangat penting dalam mendorong hasil pembelajaran sains - Jayanti, Novi Dwi; Wulandari, Ria (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how self-efficacy and learning motivation impact science cognitive learning outcomes among eighth-grade students. Using a correlational quantitative approach, the research identifies self-efficacy (X1) and learning motivation (X2) as independent variables and cognitive learning outcomes (Y) as the dependent variable. Sampling involves simple random sampling, with data collected through questionnaires and documentation. Analysis stages include normality and linearity tests, followed by correlation tests using SPSS Version 26. Results show a positive and significant influence of self-efficacy and learning motivation on cognitive learning outcomes, highlighting the importance of these factors in shaping science education outcomes for eighth-grade students. Highlight: Performance Dynamics: Self-efficacy and motivation influence science learning outcomes. Quantitative Rigor: Correlational research with SPSS ensures data validity. Educational Enhancement: Insights guide curriculum adjustments for improved science education outcomes. Keyword: Self-Efficacy, Learning Motivation, Science Education, Eighth Grade Students, Correlational Research